PERBEDAAN KEMAMPUAN BERHITUNG PERMULAAN ANAK USIA 5-6 TAHUN MENGGUNAKAN MEDIA DOMINO WARNA DI TK HARAPAN BUNDA KAB LANGKAT - Fany Padilah; Isa Hidayati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the differences in the early counting skills of 5–6-year-old children through the use of colored dominoes at Harapan Bunda Kindergarten in Langkat Regency. This study employed a quantitative approach with a pre-experimental method using a One Group Pretest-Posttest design. The subjects consisted of 13 children from Group B. Data were collected through observation and documentation, and then analyzed using the Wilcoxon Signed Rank Test. The results showed that the average pretest score of 12.46 increased to 16.69 in the posttest. The Wilcoxon Signed Rank Test (2-tailed) obtained an Asymp. value of 0.001 < 0.05, indicating a significant difference before and after the use of colored dominoes. Therefore,it can be concluded that colored dominoes have a positive effect on the counting skills of 5–6-year-old children.